Effects of Swine Manure Extract by Foliar Application and Soil Drenching on Soil Chemical Properties and Variable Soil Strength of Cassava Planted Soils - Kanto, Uthaiwan; Jutamanee, Kanapol; Osotsapar, Yongyuth; Jattupornpong, Sukanya; Kaewprasit, Chongrak (Agriculture and Natural Resources, 2012)
The effects were investigated of swine manure extract (SME) application on soil chemical properties and on soil strength, which are essential to soil management for cassava. The results of one cropping study revealed that an application of SME to the soil (SSME) or a combination of soil and foliar application of SME (FNSSME) tended to increase soil organic matter, cation exchange capacity and extractable Zn, but reduced soil strength. Nine split applications of SME in both the foliar or soil regimes had no effect on soil pH, but markedly reduced electrical conductivity indicating the depletion of soluble salts. FNSSME significantly decreased available P and exchangeable K while foliar application of SME decreased exchangeable K and exchangeable Mg. FNSSME significantly increased extractable Cu, and a similar result on extractable Mn was noted in the SME-treated soil. SME improved the availability of these two micronutrients. Chemical fertilizer (standard NPK) and FNSSME treatments reduced both exchangeable Ca and Mg. Soil strength calculated from penetration energy was maintained by a soil application of aqueous swine manure extract, SSME and FNSSME but not by an application of NPK fertilizer. The long term effects of SME application as a soil drench on the chemical properties of the soil and on soil strength over longer periods should be investigated.